Children of Hope: The Odyssey of the Oromo Slaves from Ethiopia to South Africa, by Sandra Rowoldt Shell. Ohio University Press, 2018, 352 pages. ISBN: 978-0-8214-2318-9. Hardcover price: 49.95. - Girma, Hewan (African Human Mobility Review, 2021)
Sandra Rowoldt Shell’s recounting of 64 first-person narratives of enslaved Oromo (Ethiopian) children is an innovative and well-written piece of research. As the Horn of Africa is an under-researched geographic area for the study of both domestic and external slave trades, the plurality of these first-person slave narratives has much to teach the reader about the sensitive topic of African domestic slavery. While we can question if these accounts of the enslaved children (aged 10–19, with an average age of 14 at the time of the interviews) are typical, they nonetheless reveal a complicated and detailed history of slavery from the Horn of Africa.